Pemikiran Ekonomi Abu Yusuf dan IBN Adam: Eksplorasi Awal Konsep Sumber Keuangan Negara - Asmuni Mth (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2005)
Abu Yusuf and Ibn Adam have the different methodology in writing the al-Kharaj. Abu Yusuf more rationally in revealing the arguments and his economic jurisprudence formulation more realistic and independent. While Ibn Adam just refers to the ahddits and ahddts without any external and internal critique to them. Al-Kharaj may mean the source of state income and land tax. Al-Kharaj and aljizyah loaded for the zimmi, while for Muslim people obliged to submit the zakdt. al-Kharaj, jizyah and zakat contain the close meaning. However, the inherent characters of zakat deny the zakat its self from al-kharaj or al-jizyah.